DIGITIZATION OF HOUSING CONSTRUCTION IN RURAL AREAS AND IMPROVEMENT OF MANAGEMENT EFFICIENCY - Normurodov Sarvar Norboy o’g’li; Rafiqov Rustamjon Azamjon o’g’li (Scholar Express Journals, 2023)
In this article, the construction of housing in rural areas, digitization of housing, increasing the efficiency of housing management, the nature and formation of the labor market in housing, the causes of unemployment, its reduction, words such as horizontal integration and project in housing construction are covered
Keywords: housing maintenance; housing maintenance in rural areas; digitization of housing; the nature and formation of the labor market in housing